2017
DOI: 10.1007/s00414-017-1556-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stature from femur length measured using computed tomography after the analysis of three-dimensional characteristics of femur bone in Korean cadavers

Abstract: Estimation of stature is a basic and important forensic procedure in identifying decomposed or skeletonized bodies. Due to advances in radiologic equipment, forensic science frequently uses computed tomography (CT) and software to apply these findings to investigations. Technical developments have increased the accuracy of the measurement of various bones. However, there are still some inaccuracies, such as defining correct landmarks in three-dimensional (3D) images. Femur length is frequently used for calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
0
8
2
Order By: Relevance
“…These studies provide abundant comparable data to look into the correlations of different skeletal elements for stature estimation. Among them, the equations based on femoral length resulted in the SEE values of 3.21–3.47 cm in Korean population and 3.29–3.85 cm in Japanese population , which represents the best performances among all the other equations using other irregular bones (Table ). In line with the results from the previous studies, the SEE values obtained from the equations based on femoral length in our present study ranged from 3.53 to 4.40 cm.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These studies provide abundant comparable data to look into the correlations of different skeletal elements for stature estimation. Among them, the equations based on femoral length resulted in the SEE values of 3.21–3.47 cm in Korean population and 3.29–3.85 cm in Japanese population , which represents the best performances among all the other equations using other irregular bones (Table ). In line with the results from the previous studies, the SEE values obtained from the equations based on femoral length in our present study ranged from 3.53 to 4.40 cm.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding stature estimation, CT techniques have been applied on the cranium, cervical vertebra, scapula, clavicle, sternum, metacarpals, pelvis, sacrum, and upper and lower limb lengths in various populations such as the Italian, Swiss, Egyptian, Turkish, Japanese, Chinese, Korean, and Nepalese populations . These studies provide abundant comparable data to look into the correlations of different skeletal elements for stature estimation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in our formula, the correlation between metatarsal length and stature was statistically significant, but the correlation coefficient (R) was slightly lower than that of other races. Although studies on estimating the stature of the Korean population are very rare, it has been reported that the R-value in the formula for estimating the stature by measuring the femur length from cadavers using computed tomography was high, ranging from 0.85 to 0.89 [ 36 ]. Consequently, our results indicate that metatarsal length from digital radiographs do not provide a very highly reliable method for estimating stature in the Korean population.…”
Section: Discussionmentioning
confidence: 99%